Implementasi Pemetaan Mutu PAUD di Masa Pandemi Covid 19 - rosida nur syamsiyati (BUANA GENDER : Jurnal Studi Gender dan Anak, 2020)
Early childhood education has an important role in encouraging optimal growth and development of children and preparing them to enter the next level, so that proper and quality education is needed. The purpose of this study was to find out how the implementation of the quality mapping of early childhood education in Tawangsari District, Sukoharjo Regency during the Covid 19 pandemic. Quality measurement was carried out in several stages, namely EDS data entry by education units, field verification by verifiers, data analysis and report preparation recommendation, exposure to mapping results. The results of the mapping of the quality of early childhood education in Tawangsari District were declared good and feasible to proceed to the supervision stage.Â